AI-Supported Digital Learning Environments to Enhance Scientific Literacy and Critical Thinking in Science Education - Utami, Ayu Rischi (Scientica Education Journal, 2025)
This study aims to examine the effectiveness of AI-supported digital learning environments in enhancing students’ scientific literacy and critical thinking skills in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using AI-supported digital learning integrated with inquiry-based activities and a control group taught using conventional methods. Data were collected through a scientific literacy test and a critical thinking skills test. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, AI-supported learning environments significantly enhanced students’ abilities in data interpretation, evaluation, and problem-solving. These findings suggest that integrating artificial intelligence with inquiry-based digital learning is an effective strategy to promote meaningful learning and develop essential 21st-century competencies in science education.